Noninvasive imaging of protein–protein interactions in living subjects by using reporter protein complementation and reconstitution strategies - Paulmurugan, R. (National Academy of Sciences, 2002)
In this study we have developed bioluminescence-imaging strategies to noninvasively and quantitatively image protein—protein interactions in living mice by using a cooled charge-coupled device camera and split reporter technology. We validate both complementation and intein-mediated reconstitution of split firefly luciferase proteins driven by the interaction of two strongly interacting proteins, MyoD and Id. We use transient transfection of cells and image MyoD–Id interaction after induction of gene expression in cell culture and in cells implanted into living mice. Techniques to study protein–protein interactions in living subjects will allow the study of cellular networks, including signal transduction pathways, as well as development and optimization of pharmaceuticals for modulating protein–protein interactions.